Conflicting Identities: Challenges and Coping Strategies Among Multiethnic Youth in Israel. - Malul, Shenhav; Sokar, Shireen (Journal of Loss & Trauma)
For adolescents, developing a strong and positive ethnic identity is a crucial life task that significantly impacts their well-being. This task can be especially challenging for those from multiethnic families in areas with social divisions and political conflicts. This qualitative study applies the Identity Process Theory to better understand the social-psychological challenges and coping strategies employed by adolescents from multiethnic families (an Arab father and a Jewish mother) in Israel. Twenty adolescents aged 12–18 (60% boys; mean age = 15.2 years, SD = 1.9) residing in Arab localities in southern Israel participated in semi-structured interviews about their experiences during the "Swords of Iron" war. Participants were recruited using a snowball sampling method. The results revealed four main themes reflecting the challenges faced by these adolescents, as well as four main coping strategies. Collectively, the twenty multiethnic adolescents expressed difficulties navigating their conflicting identities, experiencing peer rejection, displaying negative emotions due to the political situation, and witnessing tension and conflicts between their parents. The coping strategies employed by these adolescents included flexing their ethnic identity, disengagement and avoidance, confronting the situation, and seeking family support. Although findings are based on a nonrepresentative sample, they offer valuable insights for developing interventions and culturally sensitive practices to promote effective coping strategies that may foster resilience in adolescents from multiethnic families living in conflict regions.